Strengthening caesarean birth: Sub-Saharan Africa health system evaluation: Scoping review - Patrick Minani; Andrew Ross (AOSIS, 2024)
Background: Promoting safe caesarean birth (CB) is a challenge in sub-Saharan Africa (SSA) where maternal and neonatal mortality rates are high due to inadequate maternal health services. Although the CB rate in SSA is lower than the World Health Organization (WHO) recommendation, it is often associated with high maternal and neonatal mortality. Aim: The aim of this scoping review was to report on the extent to which SSA health systems deliver safe CB. Methods: A systematic search across various databases identified 53 relevant studies, comprising 30 quantitative, 10 qualitative and 16 mixed methods studies. Results: These studies focused on clinical protocols, training, availability, accreditation, staff credentialing, hospital supervision, support infrastructure, risk factors, surgical interventions and complications related to maternal mortality and stillbirth. CB rates in SSA varied significantly, ranging from less than 1% to a high rate of 29.7%. Both very low as well as high rates contributed to significant maternal and neonatal morbidity. Factors influencing maternal and perinatal mortality include poor referral systems, inadequate healthcare facilities, poor quality of CBs, inequalities in access to maternity care and affordable CB intervention. Conclusion: The inadequate distribution of healthcare facilities, and limited access to emergency obstetric care impacted the quality of CBs. Early access to quality maternity services with skilled providers is recommended to improve CB safety. Contributions: This scoping review contributes to the body of knowledge motivating for the prioritization of maternal service across SSA.